Teresa LÓPEZ-PELLISA, ed., "Historia de la ciencia ficción en la cultura española". Madrid, Iberoamericana, 2018. 523 pp. - Saldías Rossel, Gabriel Alejandro (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The following text is a review of the recently published volume edited by Teresa López-Pellisa (2018) dedicated to the study of the history of Spanish science fiction.
Keywords: science fiction; history; culture; Spain